A review on hydrogen as a fuel for automotive application (2014)
Hydrogen can be described as the best alternative to the conventional fuels used to power automobiles for several reasons, and these include its higher heating values and emission free combustion. It has been demonstrated as a viable automotive fuel in three technological modes: hydrogen internal combustion engines (HICEs) connected mechanically to conventional vehicles; fuel cells that produce electricity to power electric vehicles; and hybrids that involve combinations of engines or fuel cells with electrical storage systems, such as batteries. The main drawbacks of using hydrogen as a transportation fuel are huge on-board storage tanks. Hydrogen stores approximately 2.6 times more energy per unit mass than petrol but it needs an estimated 4 times more volume than petrol to store that energy. In this review, the properties and the pathways for hydrogen use in vehicles, factors affecting the commercialization of hydrogen vehicles, which are not limited to the production; storage; transportation and distribution of hydrogen; costs of production, storage and distribution; and its safety, were discussed.